2022
DOI: 10.3920/bm2021.0159
|View full text |Cite
|
Sign up to set email alerts
|

Mild intermittent hypoxia exposure alters gut microbiota composition in men with overweight and obesity

Abstract: Results from high altitude studies in humans and controlled animal experiments suggest that hypoxia exposure induces alterations in gut microbiota composition, which may in turn affect host metabolism. However, well-controlled studies investigating the effects of normobaric hypoxia exposure on gut microbiota composition in humans are lacking. The aim of this study was to explore the impact of mild intermittent hypoxia (MIH) exposure on gut microbiota composition in men with overweight and/or obesity. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…In line with our findings, a randomized clinical trial showed that although 7 days of mild IH exposure did not affect microbial diversity in overweight or obese men, it did lead to a marked increase in the abundance of specialized anaerobic bacterial genera. 39 Furthermore, previous animal experiments observed that the mice treated with IH combined with HFD were lighter than those on HFD alone, 40 , 41 contrary to our findings. These experiments were conducted with IH and diet intervention at the same time, whereas our research commenced with the HFD intervention to establish the DIO animal model before IH exposure, thereby excluding the involvement of obesity-resistant animals and precisely focusing on obese individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our findings, a randomized clinical trial showed that although 7 days of mild IH exposure did not affect microbial diversity in overweight or obese men, it did lead to a marked increase in the abundance of specialized anaerobic bacterial genera. 39 Furthermore, previous animal experiments observed that the mice treated with IH combined with HFD were lighter than those on HFD alone, 40 , 41 contrary to our findings. These experiments were conducted with IH and diet intervention at the same time, whereas our research commenced with the HFD intervention to establish the DIO animal model before IH exposure, thereby excluding the involvement of obesity-resistant animals and precisely focusing on obese individuals.…”
Section: Discussioncontrasting
confidence: 99%